Effect of Anesthesia on Endoscopic Sinus Surgery Hemostasis: a State-of-the-Art Review - Sousa-Machado, André (2023)
Endoscopic sinus surgery (ESS) is the gold standard for the management of chronic rhinosinusitis, nasal polyposis, and other pathology involving paranasal sinus as tumors. Intraoperative bleeding during ESS can be challenging due to the narrow sinonasal surgical field, single working hand, and the use of endoscopic instruments, which may affect hemostasis. There is a role for the type of anesthesia technique used for intraoperative bleeding control. Total intravenous anesthesia (TIVA) and inhalational anesthesia (IA) are some of the techniques available for anesthetic purposes. While both techniques have their advantages and disadvantages, there is a need to compare their efficacy and safety to determine which technique is more appropriate for ESS. In this review, our main focus was to summarize the current evidence about the different techniques of anesthesia used during ESS. A systematic review of the PubMed/MEDLINE database was performed using specific English terms related to TIVA and IA/volatile anesthesia used during ESS. A total of 548 publications were considered. Among these, 329 studies did not fulfill the criteria for inclusion in the systematic review, resulting in the inclusion of only 132 publications: 13 systematic reviews, 32 reviews, 92 randomized controlled trials, and 13 meta-analyses. The state of the art favors the use of TIVA during ESS due to its significant improvement in the intraoperative surgical field with less blood loss. Further studies aim to compare long-term nasal status with objective tools, ideally in similar pathology with the same surgeon.